1, 1, 1, 3, 3, 3‐Hexafluoroisopropanol as a Remarkable Medium for Atroposelective Sulfoxide‐Directed Fujiwara–Moritani Reaction with Acrylates and Styrenes. Issue 5 (18th December 2015) - Dherbassy, Quentin; Schwertz, Geoffrey; Chessé, Matthieu; Hazra, Chinmoy Kumar; Wencel‐Delord, Joanna; Colobert, Françoise
Abstract: Axially chiral biaryls are ubiquitous structural motifs of biologically active molecules and privileged ligands for asymmetric catalysis. Their properties are due to their configurationally stable axis, and therefore, the control of their absolute configuration is essential. Efficient access to atropo‐enantioenriched biaryl moieties through asymmetric direct C−H activation, by using enantiopure sulfoxide as both the directing group (DG) and chiral auxiliary, is reported. The stereoselective oxidative Heck reactions are performed in high yields and with excellent atropo‐stereoselectivities. The pivotal role of 1, 1, 1, 3, 3, 3‐hexafluoropropanol (HFIP) solvent, which enables a drastic increase in yield and stereoselectivity of this transformation, is evidenced and investigated. Finally, the synthetic usefulness of the herein disclosed transformation is showcased because the traceless character of the sulfoxide DG allows straightforward conversions of the newly accessed, atropopure sulfoxide‐biaryls into several differently substituted axially chiral scaffolds. Abstract : Influential solvent : Efficient access to atropo‐enantioenriched biaryl moieties through asymmetric direct C−H activation, by using enantiopure sulfoxide as both the directing group and chiral auxiliary, is reported (see scheme). The key role of 1, 1, 1, 3, 3, 3‐hexafluoropropanol (HFIP) solvent is investigated.